EXPRESSION OF A PERSON’S MENTAL STATE IN ARTISTIC TEXTS IN ENGLISH AND UZBEK - Saidolimova Nazirakhan Erkinjon kizi (Journal of new century innovations, 2023)
Abstract: This article provides information about the expression of the mental state of a person in English and Uzbek literary texts.